Praperadilan Sebagai Salah Satu Upaya Perlindungan Hak-Hak Tersangka Dalam Pemeriksaan Di Tingkat Penyidikan (Studi Pengadilan Negeri Medan) - Sahri Sebayang (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2020)
AbstractThe forced efforts carried out in Investigations and Prosecutions by the competent authority can be controlled through the Judiciary.The purpose of this institution was established so that the rights of the suspect could be protected, especially in the case of illegal arrest and detention as well as the cessation of investigation and prosecution. Although the institution has been regulated in positive law (Law Number 8 of 1981), but in its application there are still weaknesses both in its formulation and in its application in court so that there is no protection of human rights for suspects.This study discusses the issue of how the pretrial authority before and after Decision Number 21/PUU-XII/2014, how is the role of pretrial as an effort to protect the rights of suspects in investigations at the investigation level, what factors are obstacles to the protection of pre-trial suspect rights and how to solve them.This research uses descriptive method through literature study and field study to obtain data by holding questions and answers (interviews) with judges in the jurisdiction of Medan District Court.The results showed that the pretrial authority before Decision Number 21/PUU-XII/2014 is regulated in Article 77 through Article 83 of the Criminal Code, which is about the validity of an arrest and / or detention, the validity of the termination of an investigation or the cessation of prosecution at a request for the sake of law and justice, request for compensation or compensation rehabilitation by the suspect or his family or other party for his power of attorney whose case has not been submitted to the court. After the issuance of the Constitutional Court’s ruling Number 21/PUU-XII/2014 added to the determination of the suspect, search and seizure, including as apretrial object. The role of pretrial as one of the efforts to protect the rights of the suspect in the investigation at the investigation level to provide legal protection to immediately get an examination for furthermore can be submitted to the Public Prosecutor. The inhibiting factors regarding the protection of the rights of pretrial suspect are the lack of pretrial practice, differencesin the basic considerations of judges in passing decisions, and limited short time in pretrial hearing.Key-Words: Pretrial, Suspect Rights, Investigation.